2004
DOI: 10.1097/00002030-200409240-00005
|View full text |Cite
|
Sign up to set email alerts
|

The impact of initial highly active antiretroviral therapy on future treatment sequences in HIV infection

Abstract: There is a high rate of treatment modification among patients initiating HAART. The initial use of NNRTI-based HAART was associated with more durable treatment and lower rates of virological failure, which may translate into a reduced need for multiple salvage therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
1
11
2
1
Order By: Relevance
“…Cohort studies have shown that the use of NNRTI-based HAART as initial antiretroviral treatment resulted in a more durable response and lower rate of failure [9] and higher rates of viral suppression in comparison with single-PI regimens even after controlling for adherence [10]. In addition, subjects treated with NNRTI exhibited a lower risk of virological failure in comparison with PI-treated patients with comparable levels of adherence [11].…”
Section: Discussionmentioning
confidence: 99%
“…Cohort studies have shown that the use of NNRTI-based HAART as initial antiretroviral treatment resulted in a more durable response and lower rate of failure [9] and higher rates of viral suppression in comparison with single-PI regimens even after controlling for adherence [10]. In addition, subjects treated with NNRTI exhibited a lower risk of virological failure in comparison with PI-treated patients with comparable levels of adherence [11].…”
Section: Discussionmentioning
confidence: 99%
“…[30] Similar trends have been observed for first-line therapy, in that subjects starting NNRTI therapy remained on their initial regimens longer (median time to change 2.1 vs 1.6 years; log rank p = 0.03) compared with PI-based therapy. [31] However, such broad statements need to be interpreted with caution, given the individual toxicity profiles of drugs within both the NNRTI and PI drug classes.…”
Section: Specific Toxicity Profiles Of Nnrti Drugs: Efavirenz and Nevmentioning
confidence: 99%
“…In addition, 91% of patients with these two response predictors had at least a 0.5 log 10 viral load reduction by week 2 with a maximum treatment response of 2.03 log 10 . Consistent with earlier studies, bevirimat was well-tolerated, with a safety profile comparable to placebo through the 14 days of treatment.…”
Section: Clinical Trials and Current Status Of Bevirimatmentioning
confidence: 98%
“…8 Introduction of highly active antiretroviral therapy (HAART), which employs a combination of drugs with different targets, was a major beneficial advance that improved both the quality and length of patient survival. 9,10 However, virus isolates resistant to the approved drugs eventually appear and reduce the choice and effectiveness of treatment options. 11 It is estimated that up to 78% of HIV-1-infected individuals harbour drug-resistant virus with a rapidly growing subgroup (5-10%) exhibiting resistance to all classes of RT and PR inhibitors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation